2018
DOI: 10.1002/app.46828
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate)/wood flour composites: Effect of interface modifiers

Abstract: A fully biodegradable and biobased wood plastic composite based on a microbial biopolyester matrix, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), and a lignocellulosic filler, pine wood flour (WF), was manufactured using extrusion at industrystandard level of wood content. The effects of three compatibilization techniques on the mechanical properties of the composites were investigated. Techniques include silicone fiber treatment using Sigmacote, maleic anhydride (MA) grafting of PHBV matrix, and the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Chan et al studied the compatibilizing system with PHBV (poly-hydroxybutyrate-co-hydroxyvalerate) and wood powder as the main substrates. It was found that when the content of 4, 4-methylenebis (phenyldiisocyanate) (MDI) was 2 wt %, the tensile strength of the composite increased by 256%, but when the content was 4 wt %, it returned to the original state [27].…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al studied the compatibilizing system with PHBV (poly-hydroxybutyrate-co-hydroxyvalerate) and wood powder as the main substrates. It was found that when the content of 4, 4-methylenebis (phenyldiisocyanate) (MDI) was 2 wt %, the tensile strength of the composite increased by 256%, but when the content was 4 wt %, it returned to the original state [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the case of reactive compatibilizers, chemical bonds between the fillers and polymer matrix are formed and the overall performance of the composite can be remarkably improved [47]. For instance, the maleic anhydride (MA) grafting of PHBV matrix prior to extrusion has successfully increased the hydrophilicity of the biopolyester matrix making it more compatible with lignocellulosic fillers [48].…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of interface adhesion in NFRP or WPC can be achieved by several strategies: on one hand, by lowering the hydrophilicity of the filler/reinforcement and on the other hand, by promoting chemical interactions between the filler/reinforcement and the polymer matrix. To achieve this objective several approaches can be used, such as selective surface modification of fillers, modification of the polymer matrix by additives and using compatibilizers to provide increased interactions among the polymer-particle interface [9]. A typical matrix modification is graft copolymerization of the base polymer with maleic anhydride (MA), which can be obtained by reactive extrusion [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%